Prediction modeling for moisture sorption isotherms of rice starch/carboxymethyl cellulose from durian rind blend films - Rungsiri Suriyatem (2018)
Rice starch/carboxymethyl cellulose from durian rind (RS/CMCd) blend films were prepared by solution casting. The effect of different ratios between rice starch and CMCd (100:0, 88:12, 67:33, 50:50, 33:67, 12:88 and 0:100) on moisture sorption isotherm of blend films was investigated. The sorption isotherm of RS/CMCd blend films was determined at various relative humidity (RH) at 25°C. The isotherm curves revealed that the highest equilibrium moisture content (EMC) was obtained from CMCd film, at a w =85. Knowledge of sorption isotherms is important to predict the moisture sorption properties of the films via moisture sorption empirical models. The Lewicki, Peleg, Guggenheim-Anderson-deBoer (GAB), Brunauer-Emmett-Teller (BET), and Oswin models were tested to fit the experimental data. The root mean squares percentage error (%RMS) of Lewicki, Peleg, GAB, BET and Oswin was in the range of 5.3-83.1, 2.2-20.0, 6.9-20.2, 3.4-26.4 and 4.7-41.2, respectively. The Peleg model was found to be the best fitted model for RS/CMCd blend films. © (2013) Trans Tech Publications, Switzerland.